Pengaruh Cash Holding, Profitabilitas, Kompensasi Bonus, dan Ukuran Perusahaan terhadap Perataan Laba - Ariana Rahima; Febryanti Simon (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research intends to analyze the influence of cash holding, profitability, bonus plan, and firm size on the practice of income smoothing. This study employs a quantitive approach and utilizes secondary data from real estate and property sector that is listed on the Indonesia Stock Exchange for the period 2019 – 2022. The sample selection is determined using purposive sampling techniques, resulting in 23 companies with a total of 93 observation data. The data analysis method that this research used is binary logistic regression with the help of SPSS 26 application. The model used to determine income smoothing practices is the Eckel Index (1981). The results of this research indicate that, partially, cash holding has a significant positive effect on earnings management with a significance value of 0.000 (less than 0.05). Bonus plan has a significant positive influence on earnings management with a significance value of 0.002 (less than 0.05). Meanwhile, profitability variable exhibits a significant negative impact on earnings management with a significance value of 0.003 (less than 0.05), and company size has a significant negative influence on earnings management with a significance value of 0.035 (less than 0.05). In this research, cash holding, profitability, bonus plan, and firm size simultaneously have a significant effect on income smoothing.